African youth agripreneurs forum_announcement of shortlisted agripreneurs - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
Abidjan, Cote d’Ivoire / Ibadan, Nigeria, 20 April 2017 – Youth from all over Africa will come together in the first-ever African Youth Agripreneurs (AYA) Forum in Ibadan, Nigeria, on 25-26 April 2017. The forum provides an opportunity for the youth to show their skills, creativity, and innovativeness in agribusiness, and also relate with other youths, development partners, and stakeholders in the sector.